2012
DOI: 10.1007/s13539-012-0071-9
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cachexia is associated with a decrease in skeletal muscle mitochondrial oxidative capacities without alteration of ATP production efficiency

Abstract: BackgroundCancer cachexia is a complex syndrome related to a negative energy balance resulting in muscle wasting. Implication of muscle mitochondrial bioenergetics alterations during cancer cachexia was suggested. Therefore, the aim of this study was to explore the efficiency of oxidative phosphorylation in skeletal muscle mitochondria in a preclinical model of cancer cachexia.MethodsBerlin–Druckrey IX rats with peritoneal carcinosis (PC) were used as a model of cancer cachexia with healthy pair-fed rats (PF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
100
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(113 citation statements)
references
References 39 publications
4
100
1
Order By: Relevance
“…This contrasts with findings in humans where significant intramyocellular lipid accumulation occurs in later stages of cachexia 29,39 which has been speculated to be a consequence of alterations to mitochondrial oxidative capacity found in advanced states of cachexia. 28 That ubiquitin-proteosome-dependent proteolysis is an ATPconsuming process may explain the increased expression of markers of lipid uptake and utilization in muscle in early cachexia when proteolysis, accompanied by anorexia, commences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This contrasts with findings in humans where significant intramyocellular lipid accumulation occurs in later stages of cachexia 29,39 which has been speculated to be a consequence of alterations to mitochondrial oxidative capacity found in advanced states of cachexia. 28 That ubiquitin-proteosome-dependent proteolysis is an ATPconsuming process may explain the increased expression of markers of lipid uptake and utilization in muscle in early cachexia when proteolysis, accompanied by anorexia, commences.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these studies, a gene expression profile of subcutaneous adipose tissue comparing cachectic cancer patients (»10% weight loss) to weight-stable cancer patients demonstrated genes related to fatty acid degradation and oxidative capacity were more highly expressed in cachectic patients and coincided with elevated levels of whole body fatty acid oxidation. 18 While studies of adipose tissue suggest lipolysis and oxidation of fatty acids within adipocytes may be enhanced in later stages of cachexia, studies of liver and muscle tissue suggest there is a reduction in fatty acid oxidation/oxidative capacity in hepatocytes [25][26][27] and myocytes 28 and consequently, lipid accumulation in these tissues 26,29,30 in more advanced stages of cachexia. To our knowledge, studies of lipid metabolism in adipose, liver and muscle tissues have not been reported for early stages of cachexia when weight loss is less than 10% of initial body weight and adipose tissue loss is significant, but not severe.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there are many studies in ESRD which have demonstrated association of the ghrelin and leptin levels with malnutrition (Caliskan et al 2012) and mortality (Carrero et al 2011). UCP2 expression level has not been explored in malnourished ESRD patients, but expression of UCP2 has been investigated in cancer cachectic patients and mice model (Julienne et al 2012). In our previous study, we found that inflammatory markers like TNF-a, IL-6 and IL-10 have an important role in inducing malnutrition and inflammation at both genotypic and phenotypic level (published elsewhere).…”
Section: Introductionmentioning
confidence: 99%
“…Ultrastructural alterations have been reported in muscle mitochondria of animals bearing the C26 (27) , the LLC (Pin, Busquets et al, under revision) or the Yoshida Ascited Hepatoma (AH)-130 tumors (28) . Mitochondrial uncoupling occurs and oxidative capacity decreases in the muscle of tumor hosts (29) (30) , consistently with the occurrence of a shift from oxidative to glycolytic fibers (Pin, Busquets et al, under revision). Humoral mediators contribute to mitochondrial impairment.…”
Section: Impaired Mitochondrial Functionmentioning
confidence: 82%
“…Humoral mediators contribute to mitochondrial impairment. As an example, TNFα-induced activation of NF-κB reduces muscle oxidative capacity and negatively regulates the expression of molecules relevant to mitochondrial biogenesis (29) .…”
Section: Impaired Mitochondrial Functionmentioning
confidence: 99%